Genetic evaluation of Kankrej bulls by different sire evaluation methods - UMESH SINGH; T V RAJA; B S RATHOD; H H PANCHASARA (Indian Journal of Animal Sciences, 2023)
The genetic evaluation of Kankrej bulls was done by using three different methods viz., BLUP, Wombat sire, and Wombat animal models. First lactation 305-days yields of 348 daughters born to 9 sires and calved from 2016 to 2020 were used for the analyses. For BLUP analysis, season and year of calving were considered as fixed effects, and sire was considered as random effect. The overall average estimate of 2414.40 kg was obtained in BLUP method while 2430.29 kg was obtained in both Wombat sire and animal models. The results revealed that the Wombat animal model discriminated against the sires to the maximum extent followed by Wombat sire and BLUP models. Based on the results, two Kankrej bulls viz., K.8.32 and K.8.62 can be selected as proven bulls for nominated mating for improving the milk productivity of Kankrej cattle.